THE IMPLEMENTATION OF TEACHING AND LEARNING DESCRIPTIVE TEXT AT THE 2ND YEAR OF SMP NEGERI 2 KARTASURA IN 2010/ 2011 ACADEMIC YEAR - Sari , Ika Novita (2011)
This research aims at describing three things. They are the implementation of teaching-learning process of writing descriptive text at the second year of SMP Negeri 2 Kartasura, the problems faced by the teacher, and the problems faced by the students. This research is a descriptive qualitative research. The research data in this study were collected in the form of information about the teaching-learning activities of writing descriptive text at the second year of SMP Negeri 2 Kartasura. The methods of collecting data are observation, interview and document. The result of the record shows that the implementation of teaching- learning process is conducted in four stages. They are Building Knowledge of the Field (BKOF), Modeling of the Text (MOT), Joint Construction of the Text (JCOT), and Independent Construction of the Text (ICOT). In teaching-learning process, there are six problems faced by the English teacher, namely; the passive students, the student's ability is under average, misunderstanding the explanation of the teacher, waiting for friend's work, the teacher cannot maintain the time effectively, and student's irresponsibility in conducting the task. The students also faced the problems, namely; limited vocabulary and diction, structure, different capabilities in writing, the ideas to write is less, nervous, and the lack of independence to study.